The chronic traumatic stress treatment (CTS-T): A resilience-focused, culturally responsive intervention for refugees and survivors of torture - including a mobile mental health application - Fondacaro, Karen M; Mazzula, Emily C; Weldon, Holly T (Torture Journal, 2021)
This manuscript introduces the Chronic Traumatic Stress-Treatment for refugees and survivors of torture (CTS-Treatment; Mazzulla & Fondacaro, 2018). CTS-Treatment aligns with the Chronic Traumatic Stress model (CTS; Fondacaro & Mazulla, 2018), a biopsychosocial-spiritual and culturally responsive theoretical framework designed to guide empirical investigation and intervention for refugees and survivors of torture. CTS-Treatment is designed for use by mental health clinicians working within an individual or group format. The ten modules of CTS-Treatment are in sequence; however, flexibility in implementation is strongly encouraged. The ten intervention modules include: 1) Mental Health Discussion, 2) Safety, 3) Values, 4) Behavioral Activation, 5) Coping Skills, 6) Sleep Hygiene, 7) Working with Thoughts, 8) Acceptance and Tolerance of Emotions, 9) Life-Path Exercise and Narrative Exposure, and 10) Celebration of Life. Empirical principles underlying the treatment, along with supporting research, are presented for each module. The final section of each module explains a component of a language-free mobile mental health application for refugees. Clients are encouraged to practice the mHealth app skills at the end of each session and between sessions.